Desa Tangguh Bencana: Evaluasi Peran dan Keberhasilan Mitigasi Bencana Gempa Bumi di Lombok Tengah Tahun 2018 - Lalu Budiman; Lalu Mulkan Thariq Akbar; Lalu Malik Fajar Rasyid (Universitas Hamzanwadi, 2024)
Central Lombok Regency is one of 10 regencies/cities in West Nusa Tenggrara Province which has a fairly high level of natural disaster ratio. One of the natural disasters that often occurs is earthquakes. The earthquake on Lombok Island occurred from 29 July to 9 August 2018 with a magnitude of 7.0, resulting in many fatalities and various damages to local buildings. This research was conducted to seek information about the importance of implementing preparedness in facing disasters covering the entire region, especially in disaster-resilient villages. This research uses a qualitative descriptive approach which obtains data through interviews, observation and document study. From the results of this research, it can be concluded that disaster resilient villages have a fairly effective role in overcoming natural disasters such as earthquakes in Central Lombok Regency.